EFEKTIVITAS PEMBINAAN PENDIDIKAN AGAMA ISLAM KEPADA NARAPIDANA; STUDI KASUS LEMBAGA PEMASYARAKATAN KELAS II B TANJUNGBALAI - Raudhoh, Fiza; Nahar, Syamsu; Albina, Meyniar (Scolae: Journal of Pedagogy, 2024)
The purpose of this research is to determine the planning, implementation and effectiveness of providing Islamic religious education to prisoners at the Class II B Tanjungbalai Penitentiary. This research uses qualitative research methods with an empirical research type, and is field research with a qualitative descriptive research analysis model. The research was conducted at the Class II B Tanjungbalai Correctional Institution located on Jl. Mosque, Simardan Island Tanjungbalai with research time April to June. The result of this research is a coaching plan with the aim of changing the individual into a better person. Implementation of Islamic religious education guidance for prisoners at the Class II B Tanjungbalai Penitentiary is carried out every Monday-Thursday for male prisoners, for women on Wednesdays and Fridays, with an allocation of 2 hours per day starting from 09.00-11.00 in the mosque for men and in the hall for woman. The existing activities include performing Duha prayers, learning and teaching the Koran, then teaching materials. Teaching materials vary from monotheism, worship, and so on. The methods used were lectures and questions and answers, the media used were whiteboards and loudspeakers. The effectiveness of Islamic religious education development is considered effective based on principles and measurements, as evidenced by changes in existing attitudes and the active involvement of prisoners in every religious activity, especially men. Other evidence is that there is an implementation of sustainability by former prisoners who are found to be consistent with their lives as good people.